Structural insight of glitazone for hepato-toxicity: Resolving mystery by PASS. Issue 9 (1st May 2015) - Patel, Harun; Sonawane, Yogesh; Jagtap, Rakesh; Dhangar, Kiran; Thapliyal, Neeta; Surana, Sanjay; Noolvi, Malleshappa; Shaikh, Mahamadhanif S.; Rane, Rajesh A.; Karpoormath, Rajshekhar
Graphical abstract: The mechanism of hepatotoxicity of glitazone was investigated by PASS. Abstract: Troglitazone causes severe hepatic injury in certain individuals and multiple mechanisms related to hepato-toxicity has been reported creating confusion. In the present study, the mechanism for the hepatic injury of glitazones was investigated by PASS. The results suggest that chromane containing glitazones are apoptic agonist (activating p53 by intrinsic pathway leading to the apoptosis) and those which do not contain the chromane are devoid of this. In case of hepato-toxicity by non-chromane glitazone and their metabolite such as M-3, RM-3, rosiglitazone and pioglitazone; PASS suggest that these chemicals are not apoptic agonist but they are the substrate for CYP enzyme (Phase-I Oxidative Enzyme) and Phase-II conjugating enzymes; interfering with bile acid metabolism rendering bile acid more toxic (cholestasis). This unmetabolised bile salt further initiates the process apoptosis via intrinsic and extrinsic pathway leading to the apoptosis. Immunoblot analysis further confirm our hypothesis that troglitazone (chromane containing glitazone), but not rosiglitazone and pioglitazone (non-chromane containing glitazone) increased the levels of p53 in a time-dependent manner. Hence our prediction related to the mechanism of hepato-toxicity by apoptosis and structural insight of glitazone can be helpful in improving the drug profile of this category.